Death on the table: anaesthetic registrars' experiences of perioperative death. (13th February 2017) - Jithoo, Sandhya; Sommerville, TE
Abstract : Background: A perioperative death can be a devastating event for which anaesthetists' training does not necessarily prepare them. Previous authors have documented a range of reactions to this event. This study set out to explore individual personal and professional reactions amongst a group of senior anaesthetic trainees. Methods: A qualitative methodology was employed and purposive sampling used to select participants. Ten registrars in their fourth year of specialist training in the University of KwaZulu-Natal Department of Anaesthesia were interviewed. Transcripts of the interviews were thematically analysed. Results: Themes expressed by participants fell into three broad categories: professional role (responsibility, coping, functioning after a death), relationships with patients and families (nature of the case, emotional distress, bearing bad news), and personal impact (guilt, physical sequelae, support, desensitisation). Conclusion: Participants' perceptions supported the notion of potential second (anaesthetist) and third (subsequent patient) victims after a perioperative death. These underscore the importance of the expressed need for debriefing and an interval before resuming duty. The phenomenon of desensitisation was expressed as a spectrum between being dissociated from the event and disconnected from the people involved, raising the possibility of perioperative death as a contributing factor to burnout. This study hopes to improve awareness of the potential consequences of perioperative death and the need for these consequences to be addressed.